Liquid organic fertilizer application and environmental management in Suka Sipilihen Village, Karo Regency - Patriani, Peni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Jaya Tani Farmers Group is a livestock farmer in Suka Sipilihen, Karo Regrecy. However, in the development of livestock, there are several problems, namely environmental pollution in the form of livestock feces and it affects the quality of the environment. The problem of the Jaya Tani group is that the animal feces are abundant, causing environmental pollution in the form of odors and flies and causing livestock and their brood stock to be in an unhealthy environmental condition.The purpose of this community service is: 1) Introducing fermentation technology and the application of liquid organic fertilizer, 2) increase the knowledge and skills of breeders by utilizing livestock waste, 3) Providing education farmers about the importance of responsibility to protect the environment, namely so that the public knows about law enforcement for livestock waste management. The methods used in this community service are interviews and approaches, training practices, guidance and group strengthening. The results of the dedication activities that have been achieved by training in making liquid organic fertilizers are very effective in increasing breeders' knowledge and application of liquid organic fertilizers so that farmers can comply with Law Number 32 of 2009 concerning Environmental Protection and Management, and reduce environmental pollution.